Towards competency-based education: building the Family Medicine clerkship blueprint - Ben, Angela Jornada (2017)
Objective: To elaborate a blueprint of the competencies to be developed during three months of Family Medicine Clerkship at the Federal University of Health Sciences of Porto Alegre (UFCSPA). Methods: A literature review was carried out on competency-based education, medical schools using this approach and national and international guidelines on medical education. Therefore, the applicability of the recommendations in the context of UFCSPA Clerkship was discussed. Results: Eighteen competencies were established and divided into four axes: General, Individual Approach, Family Approach, and Community Approach. Each competency was depicted in one or more components. For each component, we have identified the teaching and students’ assessment methods currently applied in Family Medicine Clerkship. Conclusions: Clerkship competencies, which were previously developed in an intuitive way, were organized in a blueprint that enables the review and adequacy of teaching methods and students’ assessment.